Role of Kupffer Cells in Driving Hepatic Inflammation and Fibrosis in HIV Infection - Zhang, Lumin; Bansal, Meena B. (Frontiers in Immunology, 2020)
While the interactions between HIV and various liver cell populations have been explored, the relevance of these interactions when patients are well-controlled on ART is less clear. Therefore, we focus this perspective on HIV-related alterations that may drive hepatic inflammation and fibrosis in aviremic patients, with a focus on Kupffer cells and Hepatic Stellate Cells. Persistent CD4+ T cell depletion in the gut resulting in increased gut permeability has been postulated to play a role in systemic immune activation in HIV patients. The liver, with its unique location, remains the gatekeeper between the gut and the systemic circulation. The resident liver macrophage, Kupffer cell (KC), is responsible for clearing and responding to these products. We propose that changes in KC biology, in the context of HIV infection, creates a mileu that drives hepatic inflammation and fibrosis in response to microbial translocation. Targeting these pathways may be helpful in improving liver-related outcomes in HIV patients.